(3GdeLGdSs - (3GHf HCHhjg Gdbej , eMeO Hf Ydj Hf GdMSjf Hf ehSi, GdTjN GdUOhb,J (B381 (3g` s
(3ChdgG (B:s
" (3YHO Gddg Hf SYjO GdYScQi , bGd CNHQfG CHh HcQ eMeO Hf GdMSf Hf OQjO bGd CNHQfG CHh MGJe bGd bjS Hf YGUe (B: (3haOJ eY LeGYI Hf Hfi Jeje Edi GdfHi Udi Gddg Ydjg hSde (B" s
(3GdfSNI HgG MhGTs
(3hGdejcQhajde Hg Jda HSjWs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B3s
Keywords: (3abg GdePGgH GdCNQis